Memorialization of V. I. Surikov in Cultural-Historical and Urban Space of Krasnoyarsk (1916–1926) - K. A. Tishkina (Научный диалог, 2024)
This article examines the process of memorializing the legacy of V. I. Surikov (1848– 1916) during the pre-revolutionary and Soviet periods. As a renowned artist, he remained connected to his homeland, significantly influencing the development of artistic life in Siberia. The focus is on the involvement of staff from the Krasnoyarsk City Museum (later known as the Museum of the Yenisei Region) in preserving the artist’s heritage, as well as their activities in 1926, marking the tenth anniversary of his death. The relevance of this study is underscored not only by an interest in the life and work of this eminent artist but also by an analysis of how his remarkable persona shaped historical memory and the cultural-historical potential of the region. Utilizing a wide range of sources, the research encompasses a significant historical period and outlines, in chronological order, a series of initiatives aimed at preserving the memory of this notable figure in his native Krasnoyarsk. The article highlights the close collaboration between the Krasnoyarsk Museum and members of the Surikov family — A. I. Surikov and O. V. Konchalovskaya. The findings conclude that without the active participation of the Museum of the Yenisei Region, preserving the memory of this distinguished local figure would have been impossible. In conclusion, it is noted that the memorialization process unfolded over an extended period, and today, the artist’s name serves as a brand for Krasnoyarsk.